MEASURING ‘MORE PROTECTION’ FOR DISABLED VICTIMS SEXUAL VIOLENCE: A COMPARISON OF INDONESIAN AND MEXICAN REGULATIONS - Ragsanjani, Ruping; Oktafadilla, Alfianissa; Wulandari, Febryka Nada; Nurfadilah, Amelia Ayu; Basyar, Ulqiya Tsabila Lil; Palacios, Samuel (Sabtida, 2025)
Disability is any individual who has physical, sensory, and intellectual limitations that cause obstacles in interacting with their environment. This article discusses the ambiguity in the phrase ‘More Protection’ for victims of sexual violence with disabilities contained in Article 5 paragraph (2) of Law No. 8/2016. This phrase does not have a clear definition, giving rise to vague norms. The purpose of this article is to provide recommendations for improving the vague phrase so that there are no different interpretations. This research uses a normative legal method with a focus on analysing laws and regulations, legal principles, and legal doctrines relating to the protection of persons with disabilities and is linked to Mexico's Ley General para la Inclusión de las Personas con Discapacidad (LGIPD), which is more explicit in describing protection for persons with disabilities. The results of the study explain that the existence of this normative ambiguity has a negative impact on the implementation of the law and protection for persons with disabilities, resulting in interpretation by law enforcement officials, legal uncertainty for victims, and gaps in protection that can lead to discrimination in the justice system.